Is There No Need to Consider the Influence of Ion Adsorption and the Hofmeister Effect for the Precise Evaluation of Membrane Potential? - Hirohisa Tamagawa; Iori Kojima; Anh Lan Duong; Bernard Delalande (Biophysica, 2025)
Within the field of physiology, it is widely recognized that the constant flow of mobile ions across the plasma membrane generates membrane potential in living cells. This understanding is a part of the membrane theory. Despite this, membrane theory does not account for the role of ion adsorption (or desorption) processes in generating membrane potential, even though ion adsorption is a key concept in basic thermodynamics. Presently, the study of physiology lacks integration with thermodynamic principles. The membrane theory posits that living cells can differentiate between Na+ and K+ by means of channels and pumps. Thus, Na+ and K+ differentially impact the membrane potential. On the other hand, the Hofmeister effect, an older and less prominent thermodynamic theory, proposes that Na+ and K+ have varying adsorption levels to biomolecules, potentially accounting for their distinct effects on membrane potential even without the involvement of channels and pumps. This concept, distinct from the traditional membrane theory and grounded in ion adsorption (desorption) alongside the Hofmeister effect, might elucidate the process of membrane potential formation. This ion adsorption (desorption) and Hofmeister effect-based idea relates to the previously overlooked Association-Induction Hypothesis (AIH). Our experimental measurements of membrane potentials using artificial cell models highlight that ion adsorption activity and the Hofmeister effect have a comparable impact on the generation of membrane potential as ion flow in the conventional physiological model, assisted by channels and pumps.